The Implication of the Divorce of Unregistered Marriages for Divorcees’ in Bali: Assessing Status, Right and Duty - Sujana, Nyoman (Fiat Justisia: Jurnal Ilmu Hukum, 2023)
This paper analyzes the settlement of palas marabian or divorce cases in Bali. This study focuses on the implication of the settlement of divorce cases settled by the Balinese Customary Law and the National Marriage Law, especially for those whose marriages have not been registered. By using the sociological jurisprudence study method, a method emphasizing the study of the law applied in a particular society, it could be explained that the divorce of the married couple whose marriage was not registered got difficulty in obtaining legal certainty from the authority of their village or Banjar. This was due to the disharmony on the rules of the Balinese customary law and state law of Indonesia. The Leaders of the traditional villages in Bali who carried out the awig-awig (the customary law of the traditional village) could not make any settlement process sine there was no decision from the court of permanent legal force (state law). On the other hand, state law implemented by court judges would not be able to accept the divorce claim if the marriage of the couple was not registered, even though the marriage was carried out and proved according to custom and religion process. As a result, the justice seekers could not get legal certainty. This condition brought implications for the divorcees’ social lives.